Impulsive Sound Detection Directly in Sigma-Delta Domain - MIRANDA, Igor Dantas dos Santos; LIMA, Antonio C. de C. (Archives of Acoustics, 2017)
Recent implementations of Sigma-delta converters have achieved low cost, low power consumption and high integration while maintaining resolution as high as in Nyquist-rate converters. However its usage implies on a pre-processing stage to demodulate the source signal delivered from Sigma-delta modulation to Pulse-Code Modulation (PCM). This work proposes an algorithm based on Discrete Cosine Transform for impulsive signal detection to be applied directly on modulated Sigma-delta bitstream, targeting to reduce computational cost in acoustic event detection applications such as gunshot recognition systems. From pre-recorded impulsive sounds in Sigma-delta format, it has been shown that the new method presents similar error rate in comparison with traditional energy-based approaches in PCM meanwhile reduces significantly the number of operation per unit of time.